2003
DOI: 10.1097/01.phm.0000091982.33232.cb
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol, but Not Olanzapine, Impairs Cognitive Performance After Traumatic Brain Injury in Rats

Abstract: Our results demonstrate the importance of the D2 receptor in cognitive recovery after traumatic brain injury. Also, the data illustrate that some classes of antipsychotic drugs may influence cognitive recovery, and further research is needed to determine the optimal pharmacologic treatment of aggression, agitation, and other pathologic behaviors in patients with traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 20 publications
4
79
0
Order By: Relevance
“…Support for this notion derives from previous work in our laboratory demonstrating that the D 2 -receptor antagonist haloperidol impedes the ability of rats to successfully navigate a water maze task to find the escape platform Kline et al, 2007aKline et al, ,2008. Water maze performance is also impaired by haloperidol in a fluid percussion model of TBI (Wilson et al, 2003). Taken together, these TBI studies from independent laboratories indicate that D 2 -receptor antagonism impairs cognitive outcome.…”
Section: Discussionsupporting
confidence: 53%
“…Support for this notion derives from previous work in our laboratory demonstrating that the D 2 -receptor antagonist haloperidol impedes the ability of rats to successfully navigate a water maze task to find the escape platform Kline et al, 2007aKline et al, ,2008. Water maze performance is also impaired by haloperidol in a fluid percussion model of TBI (Wilson et al, 2003). Taken together, these TBI studies from independent laboratories indicate that D 2 -receptor antagonism impairs cognitive outcome.…”
Section: Discussionsupporting
confidence: 53%
“…However, the effect of atypical antipsychotics on cognition is not well established in the population with TBI. In rat models, multiple administration of olanzapine did not impair cognitive function, as did haloperidol [115]. Another rat study showed deterioration of motor and cognitive performance after multiple administrations of both haloperidol and high-dose risperidone [116].…”
Section: Neurolepticsmentioning
confidence: 99%
“…Further support for this hypothesis stems from work showing that olanzapine, a third-generation APD with less-robust DA activity, did not negatively impact cognitive performance. 13 …”
Section: Phelps Et Almentioning
confidence: 99%
“…12 Aside from deleterious effects on motor performance, daily HAL treatment (15 days) after fluid percussion injury significantly delayed the acquisition of spatial learning in the Morris water maze (MWM), compared to injury alone. 13 In controlled cortical impact (CCI) injury studies, both HAL and RISP delayed motor and cognitive recovery when administered chronically and concomitantly with behavioral testing. [14][15][16] Moreover, both HAL and RISP reinstated motor and cognitive deficits in rats that appeared to be fully recovered, and the cognitive impairments lasted for at least 3 days after discontinuation of treatment.…”
Section: Introductionmentioning
confidence: 99%